The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s40430-019-1765-0
|View full text |Cite
|
Sign up to set email alerts
|

Attaining optimized A-TIG welding parameters for carbon steels by advanced parameter-less optimization techniques: with experimental validation

Abstract: Enhanced penetration potential of activated TIG (A-TIG) welding process over conventional TIG welding has made the former process preferred for welding in recent times. The quality and shape of the weld in A-TIG are not only influenced by the chemical composition of the flux, but also by the selection of welding parameters. As a variety of process parameters influence the results, a proper understanding of process performance and identification of favorable welding conditions (optimum setting of process parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…It is fundamental that heat input to a welding process will play a vital role in deciding the quality characteristics of a weldment. 18,19 Therefore, the net heat input during the process for each weld was calculated for identifying correct samples to be evaluated using the formula 20 HeatInput kJ mm (2.08 kJ//mm), low, medium and high heat welded joints were identified and these samples were extracted to a size of 30 x 15 x 6 mm 3 in the transverse direction to the welded plate to explore the macro and microstructural characteristics.…”
Section: Mechanical Characterizationmentioning
confidence: 99%
“…It is fundamental that heat input to a welding process will play a vital role in deciding the quality characteristics of a weldment. 18,19 Therefore, the net heat input during the process for each weld was calculated for identifying correct samples to be evaluated using the formula 20 HeatInput kJ mm (2.08 kJ//mm), low, medium and high heat welded joints were identified and these samples were extracted to a size of 30 x 15 x 6 mm 3 in the transverse direction to the welded plate to explore the macro and microstructural characteristics.…”
Section: Mechanical Characterizationmentioning
confidence: 99%
“…Additionally, it was concluded that, as compared to conventional TIG welding, ATIG and FA-TIG welded samples using SiO 2 flux exhibited an increase in depth of penetration of 120%-130% and an increase in depth width ratio of 190%. Vora et al [13] used the JAYA algorithm to demonstrate the application potential of numerous response optimisation procedures utilising an integrated surface approach on a 6 mm thick plate. In their research, they identified various welding characteristics, including depth of penetration (DOP) and depth to width ratio (DWR) of HAZ, as well as input parameters like current, speed, and arc gap.…”
Section: Introductionmentioning
confidence: 99%
“…Patel et al [19] studied bead-on plate welding of Hastelloy C-22, 6 mm thick coupons by several A-TIG variations using four types of fluxes, including (SiO 2 , Al 2 O 3 ) as acidic oxides and (Fe 2 O 3 , and CUO) as basic oxides. It was noticed that welded samples (ATIG and FA-TIG) employing SiO 2 flux enhanced the depth of penetration by 120%-130% and the depth breadth ratio by 190% when compared with conventional TIG welding.Vora et al [20] applied response optimization processes by an integrated surface procedure using the JAYA algorithm with an A-TIG welding process framework on a 6 mm thick plate. In their experiments, they reported various welding parameters like-current, speed, arc gap, and output parameters like depth of penetration (DOP), depth-to-width ratio (DWR), etc They revealed that similar results were achieved when the JAYA algorithm was compared with TLBO (teaching-learning-based optimization).…”
Section: Introductionmentioning
confidence: 99%